Fabrication of Y6MoO12 molybdate ceramics: From synthesis of cubic nano-powder to sintering. Issue 4 (March 2020) - Sobota, P.; Guzik, M.; Garnier, V.; Fantozzi, G.; Sobota, M.; Tomaszewicz, E.; Guyot, Y.; Boulon, G.
Abstract: The family of cubic yttrium molybdate (Y6 MoO12 ) has been chosen due to the possibility of substituting Y 3+ cations by luminescent trivalent rare earth (RE 3+ ) ones and to obtain transparent optical ceramics. The goal of the paper is to find a route towards the fabrication of dense Y6 MoO12 ceramics from nano-powders and using well-known ceramic sintering techniques such as Spark Plasma Sintering (SPS) and Hot Isostatic Pressing (HIP). We have investigated in detail process of the powder preparation by a combustion method as well as the sintering processes taking into account all important sintering parameters. Evaporation of MoO3 was found to be correlated to reductive conditions or heating rate. Sintering was optimized in terms of phase composition, microstructure and porosity.